Anal cytological abnormalities and human papillomavirus infection in women living with HIV: A systematic review and meta‐analysis. Issue 4 (12th February 2022) - Gupta, Ruchika; Kaur, Avineet; Sandeep,; Singh, Sompal; Gupta, Sanjay
Abstract: Objective: To provide a summary estimate of the prevalence of anal cytological abnormalities and human papillomavirus (HPV) infection as well as their covariates in women living with HIV (WLHIV). Methods: Four databases – PubMed, Cochrane Library, ProQuest and Web of Science – were searched up to 31 May 2021 for studies reporting on the prevalence and/or covariates of abnormal anal cytology and/or anal HPV infection in WLHIV. The data were extracted independently by two authors using standardized extraction forms. Random effect models were used to estimate the summary effect sizes. Results: A total of 29 studies were included in the analysis. The overall prevalence of anal cytological abnormalities in WLHIV was 28.5% [95% confidence interval (CI): 22.8–35.5]. High‐grade cytological lesions were seen in 12.1% (95% CI: 8.5–17.2) of the abnormal smears. HPV infection (any type) in the anal samples was detected in 60.7% (95% CI: 54.1–68.0) of the samples while high‐risk HPV was found in 44.0% (95% CI: 37.6–51.5). A positive association was seen between anal cytological abnormality and factors such as receptive anal intercourse [meta‐risk ratio (meta‐RR) = 1.6, 95% CI: 1.3–1.8], having multiple sexual partners (1.6, 95% CI: 1.0–2.5), CD4 count < 200 cells/µL (4.6, 95% CI: 3.0–6.9), anal HPV (4.6, 95% CI: 2.4–8.8), abnormal cervical cytology (2.3, 95% CI: 2.0–2.8), and cervical HPV (meta‐RR 4.6, 95% CI: 2.2–9.8). Anal HPV infection was significantly associated with cervical HPV positivity (2.5, 95% CI: 1.2–5.3). Conclusions: Our results highlight the high prevalence of abnormal anal cytology and HPV infection in WLHIV. The positive association of anal cytological abnormality with parameters such as abnormal cervical cytology, cervical HPV infection and low CD4 count suggests that anal sex history and examination may be considered in WLHIV undergoing screening for sexually transmitted infection and possessing any of these risk factors.